An Attempt to Impart Engineering Drawing Standards Through Problem Based Learning Approach - M. L., Shreeshail; H. K., Suresh; Hiremath, Gurupadayya; Halemani, Balachandra S.; Kotturshettar, B. B. (Journal of Engineering Education Transformations, 2021)
Engineering drawing courses need to address the student’s expectations and maintain their interest. The first year engineering students at KLE Technological University undergo a 3 credit laboratory course on engineering drawing i.e. Computer Aided Engineering Drawing (CAED). This course involves manual drawing augmented with learning a drafting tool. Problem-based learning (PBL) approach, a promising new teaching approach which fuels the students learning capabilities is gaining attention of many leading technological universities. This PBL approach is introduced in teaching the CAED and the reactions are studied. Drawing standards and techniques were taught manually. After introducing PBL approach in our course and looking into the learners responses, we see improvement in the interest level of students and also in nurturing the skills required to address the problem. A real-world problem involving a route map was given to the students before teaching the drawing standards and students were asked to solve the problem. After teaching the basic of engineering drawings, the real-world problem was updated to a complex problem. Students provided solution with lot of curiosity and attentiveness. This facilitation of student friendly teaching-learning environment is most desired by any academician. The PBL approach to teach a technical drawing course is quite interesting not only for the learners but also for the instructors. The optimal PBL teaching approaches to these kinds of courses need more careful implementation steps. This small attempt to impart the drawing standards to learners using PBL route is successful looking into their responses to the problems.